GENDER DIFFERENTIALS AND PROFITABILITY ANALYSIS OF PEPPER (Capsicum species) PRODUCTION, KADUNA STATE, NIGERIA - Olugbenga, Alabi Omotayo; Chinwe Edith, Anekwe (Journal of Agricultural Sciences (Belgrade), 2023)
This study analyzed gender differentials and profitability of pepper (Capsicum species) production in Kaduna State, Nigeria. The specific objectives were to: determine the socio-economic characteristics of pepper farmers, analyze the gender differentials in costs and returns of pepper production, evaluate gender differentials in factors influencing output of pepper production, evaluate gender differentials in elasticities of production and return to scale of pepper production, and determine the constraints faced by pepper farmers in the study area. Multi-stage sampling technique was adopted. One hundred pepper farmers were selected. Primary sources of data were employed with the aid of well-designed and well-structured questionnaire. Data were analyzed using descriptive statistics, farm budgetary technique, financial analysis, Cobb-Douglas production model, elasticities of production, return to scale, and principal component analysis. The results show that 66% of pepper farmers were between 21 to 50 years. The mean age was 44 years, this implies that pepper farmers were active, energetic, resourceful and in their youthful age. Averagely, pepper farmers have 1.01 hectares of farm land, this signifies that they are smallholder, smallscale, peasant and resource-poor farmers. Pepper production was profitable in the study area. Gender differentials in average costs and returns in pepper production revealed that gross margin were 137, 556.51 Naira per hectare for male pepper farmers, higher than that at 109,711.77 Naira per hectare for female pepper farmers respectively. The net farm income was evaluated at 103, 141.46 Naira per hectare for male pepper farmers, also higher than that at 82, 418.15 Naira per hectare for female pepper farmers respectively. The rate of return on investment in pepper production was calculated at 0.55 for male pepper farmers, and 0.54 for female pepper farmers respectively. Gender differentials in factors influencing output of pepper produced shows that age , fertilizer input , were significant factors influencing output of pepper produced by male farmers at 1% probability levels, while age , labour input , and fertilizer input , were significant factors influencing output of pepper produced by female farmers at 1% probability levels respectively. The return to scale  of pepper production was estimated at 2.798 for male farmers, which signifies increasing return to scale.  The return to scale  was calculated for female pepper farmers at 0.033, which implies decrease return to scale. Constraints faced by pepper farmers were: lack of fertilizers, pest and disease infestations, inadequate capital, high perishability of commodity, poor soil fertility, lack of improved seeds, and lack of storage facilities. The study recommends that farm inputs should be provided for male and female pepper farmers such as improved seeds, fertilizer inputs, and chemical inputs, to increase productivity. Women pepper farmers should be giving more access to credit facilities at low interest rate to increase productivity. Storage facilities should be provided for pepper farmers to solve the problem of high perishability of commodity.